If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -4w)(5x + 7w) = 0 Reorder the terms: (-4w + 3x)(5x + 7w) = 0 Reorder the terms: (-4w + 3x)(7w + 5x) = 0 Multiply (-4w + 3x) * (7w + 5x) (-4w * (7w + 5x) + 3x * (7w + 5x)) = 0 ((7w * -4w + 5x * -4w) + 3x * (7w + 5x)) = 0 Reorder the terms: ((-20wx + -28w2) + 3x * (7w + 5x)) = 0 ((-20wx + -28w2) + 3x * (7w + 5x)) = 0 (-20wx + -28w2 + (7w * 3x + 5x * 3x)) = 0 (-20wx + -28w2 + (21wx + 15x2)) = 0 Reorder the terms: (-20wx + 21wx + -28w2 + 15x2) = 0 Combine like terms: -20wx + 21wx = 1wx (1wx + -28w2 + 15x2) = 0 Solving 1wx + -28w2 + 15x2 = 0 Solving for variable 'w'. Factor a trinomial. (-7w + -5x)(4w + -3x) = 0Subproblem 1
Set the factor '(-7w + -5x)' equal to zero and attempt to solve: Simplifying -7w + -5x = 0 Solving -7w + -5x = 0 Move all terms containing w to the left, all other terms to the right. Add '5x' to each side of the equation. -7w + -5x + 5x = 0 + 5x Combine like terms: -5x + 5x = 0 -7w + 0 = 0 + 5x -7w = 0 + 5x Remove the zero: -7w = 5x Divide each side by '-7'. w = -0.7142857143x Simplifying w = -0.7142857143xSubproblem 2
Set the factor '(4w + -3x)' equal to zero and attempt to solve: Simplifying 4w + -3x = 0 Solving 4w + -3x = 0 Move all terms containing w to the left, all other terms to the right. Add '3x' to each side of the equation. 4w + -3x + 3x = 0 + 3x Combine like terms: -3x + 3x = 0 4w + 0 = 0 + 3x 4w = 0 + 3x Remove the zero: 4w = 3x Divide each side by '4'. w = 0.75x Simplifying w = 0.75xSolution
w = {-0.7142857143x, 0.75x}
| 5.46/n=2.73 | | 6m=4m+16 | | f(x)=x^2+5x+10 | | .08x+.06(5000-x)=360 | | x^2+3y=3 | | x+y=2x-2y | | 2x+4-2(3+7x)-y+6+3(2x+4)=3(x+2x)+y+2(-6x-6)-3x-3y+26 | | 3x^2-73x-130=0 | | a+6=3a-2 | | 6x^2-73x-130=0 | | 6x+2+73x-130=0 | | 3y-7=2(y+4) | | -4(x+14)=2(x+10) | | 9x^2-x^2-3x=0 | | 9x^2-x^2-3=0 | | 2X-7=19x | | 35w+12w*2= | | 7/8-x=17/12 | | (y-7)(7+3)= | | 71=6x+x+x+7 | | 1/4y-11=1/10y | | 15(1.5x)+(40x)=500 | | =130+-1y | | a(3-2a)=0 | | 100=1/0,1-x | | 7/20/3 | | -7x-2x+11x=0 | | X-2-1/3(3)(4) | | (4x-5)/(3x-7)=0 | | 0.2x+6.7=5.8 | | 5x-35=7 | | 5x/3-x-2/3=9/4-1/2(x-2x-1/3) |